Holocene evolution of the shelf mud deposits in the north-western South China Sea - Li, Gang; Miao, Li; Yan, Wen (Frontiers in Marine Science, 2022)
Marine mud deposits contain rich information on past interactions between riverine sediment fluxes and marine processes. Massive mud deposits attached to a big river from South China, the Pearl River, are distributed on the north-western shelf of the South China Sea. This study examines the evolution history using cores penetrating through Holocene strata and deciphers its response to the river system, sea-level change, monsoon variations, human activities, etc. Geochemical and sedimentological data constrained by robust radiocarbon dates show the difference in the evolution of mud deposits between in shallow waters and on the middle shelf. Muddy wedges in shallow waters along the coast have formed since 7ka BP when modern current systems were established during the middle Holocene sea-level highstand. However, wide-spread muddy deposits on the middle shelf initiated after 3ka BP which are associated with enhanced sediment fluxes and strengthened winter monsoon. Human activities in recent millennia play a significant role in influencing on mud deposition on the north-west shelf of the South China Sea, evidenced by the enrichment of heavy metals in marine sediments.